THE USE OF DEIXIS IN EFL CLASSROOM INTERACTION: A PRAGMATIC STUDY OF SIXTH-SEMESTER STUDENTS OF THE ENGLISH EDUCATION STUDY PROGRAM AT NUSA NIPA UNIVERISTY - Timbu, Maria Elisabeth Ina; Balik, Lusiana Mariyeta; Kartini, Maria (Ma Chung Press, 2024)
Research has shown that EFL learners often face challenges with deictic expressions, leading to communication errors. The author wanted to examine whether similar problems exist among sixth-semester English Education students at Nusa Nipa University by analyzing the types and dominant deixis in classroom interactions. Applying Levinson's (1983) theory, this research uses Creswell's (2009) method for in-depth analysis. Data were collected through audio recordings and field notes during eight class meetings, then transcribed and coded for thematic analysis. Miles & Huberman's (1994) technique and Walizer's (1990) formula were used to measure the types of deixis and the dominant deixis used. This analysis reveals that five types of deixis are used: person deixis, time deixis, place deixis, discourse deixis, and social deixis. A total of 979 deixis were identified, with person deixis being the most dominant with 70.48%, accounting for 690 occurrences. “We” was used 194 times, reflecting the collaborative nature of group work, while ‘you’ appeared 132 times, indicating direct engagement with the audience. The findings highlight the role of deixis in shaping academic communication and interaction, emphasizing its importance in effective classrooms.